Coral Fish Community at Artificial Reef In front of Marine Field Station of Faculty of Fisheries and Marine Science UNSRAT in Kampung Ambong Likupang Village, at The District of North Minahasa - Sanjaya Molongio; Ari B. Rondonuwu; Ruddy D. Moningkey (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2021)
The aim of this study was to looking for the number of species, individual number and coral fish community structure at Artificial Reef in Front Marine Field Station of Faculty of Fisheries and Marine Science UNSRAT in Kampung Ambong Likupang Village at The District of North Minahasa. This research was done at artificial structure consist of different materials i.e iron, concrete struckture and bamboo which were laid at aproximately 9 metres. 23 coral fish species consist of : 3 species of indicator fish, 3 species of herbivorous target fish, 9 species of carnivorous target fish and 8 species mayor fish. The highest number of species was found in May 2019 (21 species) while at the same time low in individual (291) was found. In March 2019, coral fish was found in fair category (17 species) while high number of individual (383) was found in April 2019 (16 species) and the number of individual (321) was found. Diversity of all species that found from March up to May 2019 was 2,373 (good category). The dominance indeks was found 0,132 and could be categorized  as lowKeywords : Artificial, Subtrat, coral reef, fish. ABSTRAKPenelitian ini dilakukan pada substrat buatan dengan bahan yang berbeda yaitu besi, beton dan bambu yang diletakkan pada kedalaman + 9 meter. Ditemukan 23 jenis ikan karang yang meliputi  3 jenis ikan indikator, 3 jenis ikan target herbivora, 9 jenis ikan target karnivora dan 8 jenis ikan mayor. Jenis ikan karang yang tinggi ditemukan pada bulan Mei 2019 yaitu 21 jenis sedangkan jumlah individu rendah 291 individu, pada bulan Maret 2019 ikan karang yang ditemukan tergolong sedang berjumlah 17 jenis sedangkan jumlah individu tinggi yaitu 383 individu dan pada bulan April ikan karang yang ditemukan berjumlah 16 jenis dengan jumlah individu 321. Indeks keanekaragaman (H’) dari keseluruhan jenis mulai dari bulan Maret hingga Mei 2019 yaitu 2,373 dan dikategorikan sedang, indeks dominansi (D) 0,132 dan diketegorikan rendah.Kata kunci: Artifisial, Subtrat, terumbu karang, ikan.